2001
DOI: 10.1080/080352501750197601
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of iron deficiency in 12-mo-old infants from 11 European areas and influence of dietary factors on iron status (Euro-Growth study)

Abstract: A prospective longitudinal cohort study was performed to assess the prevalence of iron deficiency in European infants at 12 mo of age, and to study the influence of socio-economic status, dietary factors, growth and morbidity on iron status. The cohort consisted of 488 normal term infants from primary healthcare centres in 11 European areas. Assessed were socio-economic variables, dietary intake, anthropometry and morbidity at regular intervals from birth to 12 mo, and haemoglobin, serum ferritin, mean corpusc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
69
5
7

Year Published

2002
2002
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 147 publications
(97 citation statements)
references
References 24 publications
9
69
5
7
Order By: Relevance
“…[4,22] When compared to other developing countries, the prevalence of IDA was 72% and 69% among children in Jordan and India, respectively. [23,24] On the other hand, in developed countries the prevalence of IDA is much lower as Norway (5%), [25] United States (3.6%), [26] and average of developed European countries (7%). [27] The disturbing high prevalence of iron deficiency among our study population might be explained by the consumption of unfortified cow's milk feeding during the 1 st year of life, low intake of iron-rich foods, unmet increased needs for iron due to rapid growth, intestinal parasitic infestation or frequent consumption of tea with meals.…”
Section: Discussionmentioning
confidence: 97%
“…[4,22] When compared to other developing countries, the prevalence of IDA was 72% and 69% among children in Jordan and India, respectively. [23,24] On the other hand, in developed countries the prevalence of IDA is much lower as Norway (5%), [25] United States (3.6%), [26] and average of developed European countries (7%). [27] The disturbing high prevalence of iron deficiency among our study population might be explained by the consumption of unfortified cow's milk feeding during the 1 st year of life, low intake of iron-rich foods, unmet increased needs for iron due to rapid growth, intestinal parasitic infestation or frequent consumption of tea with meals.…”
Section: Discussionmentioning
confidence: 97%
“…On the other hand, while the iron in breastmilk is highly absorbable, the overall levels are low [26] and breastmilk contributed only 3% of the total iron intake in those who were breastfed and not consuming formula. The Euro-Growth study investigated the determinants of iron status in 12-month-old infants and reported that the most important factor positively associated with iron status was the duration of feeding of iron-fortified formula [27]. …”
Section: Discussionmentioning
confidence: 99%
“…Other studies also found an association between anemia and the intake of cow's milk. 25,26 Dietary questionnaires have limitations that must be taken into consideration. Although interviewers are trained for the task, there might be some biases in the collection of food intake data.…”
Section: Discussionmentioning
confidence: 99%